SISTEM PAKAR MENDETEKSI KERUSAKAN MESIN MOLDING TEMPERATURE SENSOR MENGGUNAKAN METODE CERTAINTY FACTOR BERBASIS WEB - rajagukguk, dormintang rajagukguk; Sitohang, Sunarsan (LPPM Universitas Putera Batam, 2021)
One of the technologies found in the industrial sector is the molding machine which is very influential on humans in helping their work. The molding machine is a useful tool for printing or shaping a product as required by the company. This machine is able to do very difficult jobs quickly or even impossible for humans to do manually. In operating the molding temperature sensor machine, humans or robots are the controllers of this machine. If the temperature sensor molding machine is not designed properly and regularly, the machine cannot work properly, does not last long, there is a possibility of fatal damage resulting in accidents to controlling employees, to other employees around and also to damage to the products the machine is working on the. An master framework is a PC based framework that utilizes information, realities, and thinking strategies in tackling issues that can normally just be settled by a specialist in a specific field. Based on the description above, the problem that will be presented or researched in compiling this thesis, the author is interested in taking the title of the research on